Semiological importance of pain during the stages of a pulpal inflammation process - Olayo Delfín Soto; Andrés O. Pérez Ruíz; Mauralina Juliana Sardiñas Valdés (Editorial Ciencias Médicas, 2020)
Introduction: Attempts have been made to diagnose the pulpal inflammatory process based on its histopathological features, but to no avail, for these findings cannot be compared with clinical results. It would be more objective and reliable to analyze the characteristics of the pain expressing the pulpal evolution at each stage and establish an accurate diagnosis allowing the choice of the type of treatment to be indicated. Objective: Interpret the course of a pulpal inflammatory process through variables associated to nociceptive stimuli. Methods: A bibliographic review was conducted about the study variables with respect to pain and its association to a pulpal inflammatory state. A total 24 scientific papers were analyzed which dealt with pulpal pain, of which 15 were selected for being the most closely related to the goal pursued and having been published in international and national journals in the last five years. PubMed was the main source searched, while other databases such as Lilacs, Hinari and Medline were also consulted. Data analysis and integration: Pulpal conditions are classified into reversible, transitional, irreversible pulpitis and necrotic pulp. Pain semiology is based on the following four basic variables associated to nociceptive stimuli: pulpal pain quality (sharp or continuous), course (intermittent or continuous), location (limited to a region in the mouth, radiating or referred) and intensity (mild, moderate or severe). Conclusions: The variables associated to nociceptive stimuli are semiologically important, for they make it possible to evaluate the painful manifestations gone through by a pulpal inflammatory process.